2019
DOI: 10.4103/jhrs.jhrs_8_19
|View full text |Cite
|
Sign up to set email alerts
|

Are we justified doing routine intracytoplasmic sperm injection in nonmale factor infertility? A retrospective study comparing reproductive outcomes between in vitro fertilization and intracytoplasmic sperm injection in nonmale factor infertility

Abstract: Introduction:Intracytoplasmic sperm insemination (ICSI) came into use in 1992 to improve fertilization in couples with male factor infertility undergoing in vitro fertilization (IVF) or in couples with fertilization failure in a prior IVF cycle. Our aim was to find out if routine ICSI has any additional benefit over conventional IVF in non male factor cases in modern Assisted Reproductive Technology (ART).Methods:This is a retrospective single centre study undertaken at a private IVF center. A total of 350 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In 2002, a meta-analysis reported that if the standard insemination concentration of 0.2 × 10 6 /mL was utilized in those with mild MF, FR was improved if ICSI was used. Yet, this was no longer applicable if a higher concentration of 0.8 × 10 6 /mL was utilized [14]. However, when comparing these results to more recent results, Esteves et al noted that those with only mild MF, 5 × 10 6 /mL to <15 × 10 6 /mL and <32% forward motility, IVF, and ICSI had no difference in FR or LBR [31].…”
Section: Mild Male Factormentioning
confidence: 88%
“…In 2002, a meta-analysis reported that if the standard insemination concentration of 0.2 × 10 6 /mL was utilized in those with mild MF, FR was improved if ICSI was used. Yet, this was no longer applicable if a higher concentration of 0.8 × 10 6 /mL was utilized [14]. However, when comparing these results to more recent results, Esteves et al noted that those with only mild MF, 5 × 10 6 /mL to <15 × 10 6 /mL and <32% forward motility, IVF, and ICSI had no difference in FR or LBR [31].…”
Section: Mild Male Factormentioning
confidence: 88%
“…Several studies have compared conventional IVF and ICSI in terms of embryonic outcomes (22)(23)(24). In most studies, there was no signi cant difference in the proportion of good-quality embryos and 2PN embryos (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Severe oligospermia and astheno-spermia were de ned as: sperm concentration 10×10 6 /ml and sperm with progressive motility rate (a+b) 10% in our clinical diagnostic criteria. A total of 30,352 cycles (22,472 conventional IVF cycles and 7,880 ICSI cycles) were included. Based on the number of oocytes retrieved, the included cycles were divided into three groups: 1-3 (n = 8,680), 4-6 (n = 1,071), and 7-9 (n = 11,101).…”
Section: Subjects and Datamentioning
confidence: 99%